Theoretical basis of simulator-analyzer building-up for microwave amplifiers and oscillators - S. V. Savelkaev; S. V. Romasko; V. A. Litovchenko; N. V. Zarzhetskaya (Известия высших учебных заведений России: Радиоэлектроника, 2017)
The construction principle of simulator-analyzer is proposed providing simulation modeling of amplifiers and oscillators in coaxial microwave measurement chain according to their technical specifications, followed by measurement of complex load reflection coefficients of the active component of the devices for their further development in microstrip design. Mathematic model of simulator-analyzer as well as mathematic model of its calibration is presented. Analysis method of active component stability in the area of its complex load reflection coefficients is considered that facilitates the choice of the loads and the most active component in simulation of amplifiers and oscillators. In addition, the possibility of using the simulator-analyzer for measuring complex reflection coefficients at the input and the output of the loaded active component is described, as well as measurement of its complex transmission coefficients which together with the measured complex load reflection coefficients allow to determine S-parameters of the analyzed component it will have when included in a micro strip line.